Transcriptome-wide microRNA and target dynamics in the fat body during the gonadotrophic cycle of Aedes aegypti - Zhang, Xiufeng (Proc Natl Acad Sci U S A, 2017)
The mosquito Aedes aegypti is a major vector of numerous viral diseases, because it requires a blood meal to facilitate egg development. The fat body, a counterpart of mammalian liver and adipose tissues, is the metabolic center, playing a key role in reproduction. Therefore, understanding of regulatory networks controlling its functions is critical, and the role of microRNAs (miRNAs) in the process is largely unknown. We aimed to explore miRNA expression and potential targets in the female fat body of Ae. aegypti, as well as their changes postblood meal (PBM). Small RNA library analysis revealed five unique miRNA patterns sequentially expressed at five sampled time points, likely responding to, and affecting, waves of upstream hormonal signals and gene expression in the same period. To link miRNA identities with downstream targets, transcriptome-wide mRNA 3′ UTR interaction sites were experimentally determined at 72 h posteclosion and 24 h PBM through Argonaute 1 cross-linking and immunoprecipitation followed by high-throughput sequencing. Several target sites were validated by means of in vitro luciferase assays with wild-type and mutated 3′ UTRs for six miRNA families. With established transgenic lines, consistent results were observed with spatiotemporal knockdown of miR-8 and luciferase assays. We further investigated miRNAs potentially regulating various physiological processes based on Clusters of Orthologous Groups functional categories. Hence, the present work comprehensively elucidated miRNA expression and target dynamics in the female mosquito fat body, providing a solid foundation for future functional studies of miRNA regulation during the gonadotrophic cycle.